2021
DOI: 10.1038/s41440-021-00708-z
|View full text |Cite
|
Sign up to set email alerts
|

Central and peripheral arterial stiffness responses to uninterrupted prolonged sitting combined with a high-fat meal: a randomized controlled crossover trial

Abstract: Independently, prolonged uninterrupted sitting and the consumption of a meal high in saturated fats acutely disrupt normal cardiovascular function. Currently, the acute effects of these behaviors performed in combination on arterial stiffness, a marker of cardiovascular health, are unknown. This study sought to determine the effect of consuming a high-fat meal (Δ = 51 g fat) in conjunction with prolonged uninterrupted sitting (180 min) on measures of central and peripheral arterial stiffness. Using a randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…As a traditional Western meal high in refined sugars and fats, all participants consumed a McDonald's Corporation breakfast meal which included a double sausage and egg McMuffin, two hash browns and a hot chocolate with added double cream (1066 kcal, 4.5 MJ, 61 g fat [of which 20 g was saturated fat], 86 g carbohydrates, 40 g protein and 5 g salt) as this has previously been shown to impair arterial function [15,23].…”
Section: Meal Typementioning
confidence: 99%
See 1 more Smart Citation
“…As a traditional Western meal high in refined sugars and fats, all participants consumed a McDonald's Corporation breakfast meal which included a double sausage and egg McMuffin, two hash browns and a hot chocolate with added double cream (1066 kcal, 4.5 MJ, 61 g fat [of which 20 g was saturated fat], 86 g carbohydrates, 40 g protein and 5 g salt) as this has previously been shown to impair arterial function [15,23].…”
Section: Meal Typementioning
confidence: 99%
“…Whilst executive function and brain blood flow decreased over time, there was no condition effect suggesting glycaemic index alone did not play a role. However, consumption of a Westernized meal high in refined sugars and triglycerides followed by 180 min of uninterrupted sitting, has been shown to significantly worsen arterial stiffness [15], and independent of sitting, impair cerebrovascular, and executive function [16]. What is not known is whether a simple desk-based mitigation strategy such as leg fidgeting may be of use in offsetting any cerebrovascular and cognitive impairment following a prolonged sitting after consuming a Westernized meal.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to exercise, dietary patterns have acute and chronic effects on vascular function. Fryer et al investigated the acute effects of a combination of prolonged uninterrupted sitting (180 min) and a high-saturated fat meal on arterial stiffness in 13 healthy nonsmoking males [ 41 ]. They reported that central arterial stiffness assessed by cfPWV and peripheral arterial stiffness assessed by PWV β were more deteriorated by consuming a high-fat meal (61 g fat, 1066 kcal) prior to prolonged uninterrupted sitting than by consuming a low-fat meal (10 g fat, 601 kcal) prior to prolonged uninterrupted sitting.…”
Section: Lifestyle Modifications and Vascular Functionmentioning
confidence: 99%
“…The typical Western diet is relatively high in both fat and refined carbohydrate content compared to diets in previous eras, ( Drewnowski and Popkin, 1997 ) and the consumption of a high-fat meal before a sitting bout is associated with increased markers of CVD risk for up to 180 min after the meal. ( Fryer et al, 2021 ) While similar research has yet to be conducted on SB and high-carbohydrate meals, some data indicates that high-carbohydrate meals followed by prolonged sitting result in elevated postprandial blood glucose responses relative to interrupted sitting, which may have cardiovascular implications. ( Dempsey et al, 2018 ) Similarly, while the behaviors of historic humans after mealtimes may be uncertain, technology has increased the options of leisure time SB following mealtimes available to modern humans.…”
Section: Characteristics Of Contemporary Sedentary Behaviormentioning
confidence: 99%